Governing poverty: compulsory income management and crime in Australia - Staines, Zoe (Critical criminology, 2021)
Welfare reforms have swept across most liberal-democratic nations over recent decades, carried by a deep neoliberal faith in market rationality and an intensive focus on the individual as a key site of disciplinary intervention. These reforms have been accompanied by discourses within which welfare, deviance and crime are interwoven tightly. Australia’s Income Management (IM) policies, which "quarantine" a portion of welfare income as a means of behavioral conditionality, provide an example of welfare policy that has been promoted as a way of reducing crime. In this article, we interrogate these claims. We find little support for the policy logic linking IM and crime, and we demonstrate that there is no clear evidence that IM has reduced crime. Instead, we argue that the overwhelming focus of IM on poor and racialized subjects serves to socially construct crime as a metaphor for justifying the harmful "double punitive regulation" of the state. This sees the state’s left hand (i.e., social functions, including workfare) and right hand (i.e., punitive functions, including prisonfare) work together to turn poor (and mainly Indigenous) populations into marketized subjects, while punishing those who resist, through a range of governing techniques.